4‐kV 100‐Mbps monolithic isolator on SOI with trench isolation for wideband networks. Issue 6 (18th September 2013) - Hashimoto, Takayuki; Yukutake, Seigo; Kanekawa, Nobuyasu; Takeuchi, Yusuke; Watanabe, Atsuo; Akiyama, Noboru
Abstract: Two types of monolithic isolator on a silicon‐on‐insulator (SOI) with trench isolation have been fabricated. One is a multitrench isolator with polysilicon resistors in which two circuit areas are isolated using thirty‐four 0.4‐µm‐wide trenches on an SOI. The inequality in the voltages applied to the trenches is reduced by using polysilicon resistors parallel to the trenches, which increases the isolation voltage from 2.6 to 4.0 kV. The other is a spiral wide‐trench isolator in which two circuit areas are isolated using two spiral 10‐µm‐wide trenches. Monocrystalline silicon is used as a resistor to reduce the inequality in the trench voltages. Signals are transmitted between the two circuit areas through two series of high‐voltage capacitors: silicon on buried oxide and a third metal are used as electrodes. A network interface large‐scale integration (LSI) with a four‐channel isolator was fabricated using multitrench isolation. It provides 4‐kV isolation and supports 100‐Mbps transmission. © 2013 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.